2020
DOI: 10.5964/jspp.v8i1.1102
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and the liberal-conservative political divide in the U.S.

Abstract: When future historians look back upon the current political climate in the U.S., it is likely that they will view the severe state of political polarization between liberals and conservatives as being one of its defining characteristics. While some have suggested that a difference in general levels of empathy among liberals and conservatives could be playing a role in shaping their differing political attitudes, psychologist Paul Bloom has forcefully argued against any such difference in his book “Against Empa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
4
21
1
Order By: Relevance
“…In addition to these primary considerations, we would like to briefly discuss some of our secondary contributions. In support of previous research, we confirmed that political conservatism is associated with lower levels of empathy [28][29][30][31][32][33][34][35], higher levels of authoritarian beliefs [48][49][50][51][52][53][54], and lower levels of several dimensions of perceived pandemic threat [1, 1 3 13-15, 17, 59-63]. Our analyses of our disaggregated conservatism index are also informative.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to these primary considerations, we would like to briefly discuss some of our secondary contributions. In support of previous research, we confirmed that political conservatism is associated with lower levels of empathy [28][29][30][31][32][33][34][35], higher levels of authoritarian beliefs [48][49][50][51][52][53][54], and lower levels of several dimensions of perceived pandemic threat [1, 1 3 13-15, 17, 59-63]. Our analyses of our disaggregated conservatism index are also informative.…”
Section: Discussionsupporting
confidence: 88%
“…The first link in our theoretical model suggests that political conservatism contributes to riskier pandemic lifestyles by reducing empathetic concern. While we are regularly inundated with popular depictions of "heartless conservatives" and "bleeding heart liberals, " research consistently shows that political conservatives tend to exhibit lower levels of compassion and empathy (i.e., less concern for the feelings and experiences of others) relative to their more liberal counterparts [28][29][30][31][32][33][34][35]. Cameron and Rapier [36,p.…”
Section: Empathymentioning
confidence: 99%
“…We did not ask respondents' occupations, but future research should explore the relationship between work experiences and empathy. Confirming earlier findings [49], and as evidenced also during the 2020 presidential election, respondents who described themselves as liberal showed higher levels of general empathy, empathetic concern, and perspective taking than respondents who described themselves as conservative. As discussions of facemask requirements and "opening up the economy" illustrate, conservatives may take the pandemic situation less seriously [47].…”
Section: Discussionsupporting
confidence: 83%
“…Engaging in coronavirus-prevention behaviors can be perceived as a cautionary measure that reduces the spread of the virus and impacts others, which in turn influences the welfare of society (Jordan et al 2020). This construal may not resonate with conservatives due to their tendency to hold people responsible for their own problems (Morris 2020) and emphasis on self-reliance (Janoff-Bulman 2009). Conservatives may infer that their actions cannot prevent others from being infected or reduce the spread of the virus because of their belief that individuals are responsible for their own outcomes.…”
Section: Conceptual Frameworkmentioning
confidence: 99%